Millimeter-Wave Printed-RGW Hybrid Coupler With Symmetrical Square Feed - Zhao, Zhenjiang; Denidni, Tayeb A. (IEEE microwave and wireless components letters, 2020)
In this letter, a new hybrid coupler with symmetrical square feed using printed ridge gap waveguide (RGW) technology is introduced and investigated. This structure can find important applications in beamforming network designs. The proposed coupler has a compact size of 1.12λ g ×1.12λ g ×0.14λ g and shows promising results at millimeter-wave Ka-band around 30 GHz, especially in terms of amplitude balance bandwidth and loss. The simulated results are compared with the measured data and a good agreement is achieved.